IGFBP2 from a novel copper metabolism-associated biomarker promoted glioma progression and response to immunotherapy - Luo, Qisheng; Zhuang, Junhong; Zheng, Dandan; Miao, Changfeng; Luo, Hongcheng; Peng, Jun; Zheng, Chuanhua; Qin, Chengjian; Lan, Chuanliu; Chen, Meiqin; Xia, Ying; Huang, Deyou; et al. (Frontiers in Immunology, 2023)
Introduction Copper metabolism encompasses all cellular metabolic processes involving copper ions and plays a significant role in the pathogenesis of diseases, including cancer. Furthermore, copper is intricately involved in various processes related to nucleotide metabolism. However, a comprehensive analysis of copper metabolism in gliomas remains lacking despite its importance. Methods To address this gap, glioma patients were stratified based on the expression levels of copper metabolism-related genes. By utilizing machine learning techniques, a novel copper metabolism-associated biomarker was developed. The potential of this biomarker in prognosis, mutation analysis, and predicting immunotherapy response efficiency in gliomas was systematically investigated. Results Notably, IGFBP2, identified as a glioma tumor promoter, was found to promote disease progression and influence immunotherapy response. Additionally, glioma-derived IGFBP2 was observed to enhance microglial migration. High IGFBP2 expression in GBM cells facilitated macrophage interactions through the EGFR, CD63, ITGB1, and CD44 signaling pathways. Discussion: Overall, the copper metabolism-associated biomarker shows promising potential to enhance the clinical management of gliomas, offering valuable insights into disease prognosis and treatment strategies.